2017
DOI: 10.1039/c7cc05951e
|View full text |Cite
|
Sign up to set email alerts
|

Highly stereoselective cyclopropanation of various olefins with diazosulfones catalyzed by Ru(ii)Pheox complexes

Abstract: A highly stereoselective cyclopropanation of various olefins with diazosulfones catalyzed by chiral Ru(ii)-Pheox complexes was developed to give chiral cyclopropyl sulfones in high yields (up to 99%) with excellent trans-selectivity and enantioselectivity (up to 98% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…A number of enantioenriched aryl‐substituted substrates ( 4 a – 4 f ) were readily prepared using Iwasa's Ru‐catalyzed asymmetric cyclopropanation of alkenes with α‐diazomethyl aryl sulfones (Scheme , Method A) . Using our α‐hydroxylation conditions, highly enantioenriched cyclopropanone equivalents 5 a – 5 f were obtained in moderate to excellent yields as single diastereomers with retention of configuration at the α‐position, as evidenced by X‐ray crystallographic analysis ( 5 a ) .…”
Section: Resultsmentioning
confidence: 99%
“…A number of enantioenriched aryl‐substituted substrates ( 4 a – 4 f ) were readily prepared using Iwasa's Ru‐catalyzed asymmetric cyclopropanation of alkenes with α‐diazomethyl aryl sulfones (Scheme , Method A) . Using our α‐hydroxylation conditions, highly enantioenriched cyclopropanone equivalents 5 a – 5 f were obtained in moderate to excellent yields as single diastereomers with retention of configuration at the α‐position, as evidenced by X‐ray crystallographic analysis ( 5 a ) .…”
Section: Resultsmentioning
confidence: 99%
“…Iwasaa employed Ru­(II)-Pheox complex ( 574 ) for the highly stereoselective cyclopropanation of alkenes ( 577 ) with various diazo precursors ( 578 / 580 / 583a ) (Scheme A–C). The asymmetric cyclopropanation between diethyl diazomethyl­phosphonate ( 578 ) and a series of alkenes including styrene derivatives, α,β-unsaturated esters, ketones, and amides was carried out to provide the corresponding cyclopropylphosphonate products ( 579 ) in high yields and with excellent diastereoselectivity (up to 99:1 dr) and enantioselectivity (up to 97% ee ) (Scheme A) . Similarly, diazosulfones ( 580 ) reacted with various alkenes including vinyl ethers, vinyl amines, and vinyl carbamates to furnish chiral cyclopropyl sulfones ( 581 ) in high yields (up to 80%) with excellent trans -selectivity and enantioselectivity (up to 96% ee ) (Scheme B) . An asymmetric synthesis of various trifluoromethyl cyclopropanes ( 584 ) was achieved in high yields with excellent diastereoselectivity (up to 98:2 dr) and enantioselectivity (up to 96% ee ) by reacting in situ generated CF 3 CHN 2 ( 583b ) with a range of alkenes including vinyl ferrocene, vinyl ethers, vinyl amines, vinyl carbamates, and dienes (Scheme C) …”
Section: Mono(oxazoline) Ligandsmentioning
confidence: 99%
“…211 Similarly, diazosulfones (580) reacted with various alkenes including vinyl ethers, vinyl amines, and vinyl carbamates to furnish chiral cyclopropyl sulfones (581) in high yields (up to 80%) with excellent trans-selectivity and enantioselectivity (up to 96% ee) (Scheme 179B). 212 An asymmetric synthesis of various trifluoromethyl cyclopropanes (584) was achieved in high yields with excellent diastereoselectivity (up to 98:2 dr) and enantioselectivity (up to 96% ee) by reacting in situ generated CF 3 CHN 2 (583b) with a range of alkenes including vinyl ferrocene, vinyl ethers, vinyl amines, vinyl carbamates, and dienes (Scheme 179 C). 213 In 2012, Iwasaa described the highly enantioselective intramolecular cyclopropanation of trans-allylic diazoacetates (585) and alkenyl diazoketones using a water-soluble Ru(II)/ hydroxymethyl (phenyl)oxazoline catalyst, Ru(II)-hm-Pheox (575) (Scheme 180).…”
Section: Scheme 174 Asymmetric Transfer Hydrogenation Of Ketonesmentioning
confidence: 99%
“…We successfully demonstrated that a series of Ru(II)–Pheox complexes could promote catalytic asymmetric intra- and intermolecular cyclopropanations of a wide variety of olefins and asymmetric Si–H insertion reactions with diazo compounds to give the desired products in high yields with high enantioselectivities. 2 On the other hand, details on the generation of the metal–carbene complex from Ru(II)–Pheox and a diazo compound in the initial stage of the reaction remain scarce. In addition, the crystallinity of the Ru(II)–Pheox complex was low and its X-ray crystal structure has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that (acetonitrile) 4 Ru­(II)–phenyloxazoline complex (Ru­(II)–Pheox), which has a unique C 1 -symmetric structure, is an efficient catalyst for carbene transfer reactions. We successfully demonstrated that a series of Ru­(II)–Pheox complexes could promote catalytic asymmetric intra- and intermolecular cyclopropanations of a wide variety of olefins and asymmetric Si–H insertion reactions with diazo compounds to give the desired products in high yields with high enantioselectivities . On the other hand, details on the generation of the metal–carbene complex from Ru­(II)–Pheox and a diazo compound in the initial stage of the reaction remain scarce.…”
Section: Introductionmentioning
confidence: 99%